PENDEKATAN SOSIOLOGI-ANTROPOLOGI DALAM TAFSIR Living Quran: Studi analisis terhadap respon netizen pada postingan akun @QuranReview di instagram - Muhammad Rifat Al-Banna; Moch. Ihsan Hilmi; Eni Zulaiha (LPPAIK Universitas Muhammadiyah Bandung, 2022)
Living Quran is a study of various social events related to the Koran which has become a tradition in forming a local entity. This study explores the living Quran which contains interpretations through digital media on the Instagram account @QuranReview. This study aims to examine the netizen's response to posts regarding the interpretation in the @QuranReview account post. In the midst of the trend of interpreting the Koran on social media, the @QuranReview account has succeeded in attracting the attention of netizens through the presentation of religious content in the form of interpretation with the style of language, diction and nuances typical of the millennial generation. The form of analysis used in this research is descriptive analysis based on a socio-anthropological approach. The findings from this study are that the netizen's response to the commentary in the @QuranReview Instagram account has three effects that can provide benefits to netizens, including cognitive effects that are able to provide new insights in understanding interpretations, then affective effects that can directly cause aesthetic and emotional dimensions when Netizens deeply interpret an interpretation, and the behavioral effects that can make changes in the perspective and behavior of netizens even more.